Sequential oxidation of humic acids by ozonation and photocatalysis - KERÇ, ASLIHAN (TAYLOR & FRANCIS INC, 2003)
In this study, humic acids, the natural polymerized organic compounds which are responsible for the formation of. disinfection by-products such as haloacetic acids and trihalomethanes upon chlorination, are oxidized in a sequential system incorporating ozonation and photocatalysis. Titanium dioxide is used as photocatalyst in the photocatalytic oxidation phase. Humic acid degradation kinetics is evaluated both for ozonation. and photocatalysis. The Freundlich adsorption model is used for defining the adsorption characteristics of humic acid solutions on the photocatalyst after the ozonation step. The Langmuir-Hinshelwood model. is also studied for explaining the adsorptive and photocatalytic removal of humic acids.
Keywords: ozone; humic acid; photocatalysis; titanium dioxide; color removal; UV254 removal; OZONE; WATER